Survey on Vortex Shedding Tabs as Supersonic Jet Control - Thangaraj, Thillaikumar; Kaushik, Mrinal; Deb, Dipankar; Unguresan, Mihaela; Muresan, Vlad (Frontiers in Physics, 2022)
This paper provides an overview of the tabs-controlled jets to understand and predict the influence of mixing promoting vortices at speeds ranging from subsonic to supersonic. A detailed description consisting of various features of the circular jets controlled by tab-like vortex generators is provided. Here, both the experimental and the numerical investigations on the impacts of tabs on the mixing enhancement and noise suppression are presented. Following a brief introduction about subsonic and supersonic circular jets, this paper discusses the influences of certain key parameters on mixing characteristics, including the effect of tab geometry, tab number, tab orientation, tab size, and tab position relative to nozzle outlet. Subsequently, their effect on noise suppression is also reviewed. The detrimental effect of tabs in terms of thrust penalty is described. Finally, the future direction of research on the tab-controlled jets is outlined.